Transitions in the heartbeat pattern during pupal diapause and adult development in the flesh fly, Sarcophaga crassipalpis - Sláma, Karel; Denlinger, David L (Journal of insect physiology, 2013)
The heartbeat of diapausing pupae of the flesh fly Sarcophaga crassipalpis was investigated using electrocardiographic methods including gravimetry, thermography, and optocardiography. During deep diapause, characterized by minimum metabolic activity, the heart exhibited discontinuous bouts of exclusively unidirectional, anterograde pulsations (40-60 contractions/min) that lasted only a few seconds. These bouts of cardiac pulsations were separated by periods of rest lasting 5-30 min. During infradian peaks of metabolic activity (4-day cycles) that occur throughout diapause, periods of rest were shortened and frequency of the anterograde heartbeat increased more than two-fold. Throughout diapause, the heart consistently exhibited a simple, bi-phasic pattern of pulsations generated by bouts of anterograde heartbeats interspersed with periods of cardiac rest. When the fly broke diapause and initiated pharate adult development, a new tri-phasic pattern was observed: the new pattern incorporated heartbeat reversal, as noted by the appearance of retrograde pulsations that directed hemolymph in a posterior direction. These retrograde heartbeats occurred exclusively in the abdominal portion of the dorsal vessel and were not observed in the head or thorax. The transition to pharate adult development was also accompanied by the appearance of extremely strong extracardiac pulsations that served a respiratory function. Although these pulsations made it more challenging to record heartbeat patterns in pharate adults, we observed progressive shortening of the resting periods and a continual increase in the rate of both anterograde and retrograde pulsations, a trend that was further magnified in the adult fly (anterograde contractions up to 300/min and retrograde contractions approximately 125/min). These results imply that the circulatory function of the heart is homeostatically regulated and is responsive to developmental changes and the diverse metabolic rate demands of larvae, diapausing pupae, pharate adults and adult flies.
Keywords: Pupa; hemolymfa; Animals; srdeční frekvence; Diapause, Insect; Female; zvířata; mužské pohlaví; Sarcophagidae; Male; Hemolymph; diapauza hmyzu; cykly aktivity; Heart Rate; kukla; ženské pohlaví; Activity Cycles